Preparation method of electrothermal strontium-lanthanum-cobalt composite catalyst for purifying VOCs in low-oxygen environment

By preparing the electric-thermal strontium lanthanum cobalt composite catalyst, the problem of the decrease in activity of existing catalysts in ultra-low oxygen environments is solved, and the efficient purification of VOCs and structural stability under low oxygen conditions is achieved, thereby reducing energy consumption and cost.

CN119701978APending Publication Date: 2025-03-28NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411873382.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The oxidation performance of existing catalysts has significantly decreased in ultra-low oxygen environments, and it is difficult to maintain catalytic activity and structural stability, making it difficult to effectively purify VOCs.

Method used

Using the preparation method of an electric heated strontium lanthanum cobalt composite catalyst, a conductive lanthanum cobalt composite oxide is obtained by mixing lanthanum salt, cobalt salt, glucose and a small amount of deionized water, and calcining is used to obtain a conductive lanthanum cobalt composite oxide, and lanthanum cobalt composite oxide, urea, and citric acid are added to the strontium salt solution to form a strontium oxide-lanthanum oxide-cobalt oxide composite catalyst.

Benefits of technology

The catalyst maintains high catalytic activity and structural stability in a low oxygen environment, can effectively decompose VOCs, reduce the energy consumption of the exhaust gas treatment system, and is low in cost, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701978A_ABST
    Figure CN119701978A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite catalysts, in particular to a preparation method of an electric heating strontium-lanthanum-cobalt composite catalyst for purifying VOCs in a low-oxygen environment, which comprises the following steps: S1, directly mixing lanthanum salt, cobalt salt and glucose in a certain proportion with a small amount of deionized water, and stirring for a period of time to form sticky slurry to obtain a mixture; s2, directly putting the mixture in the S1 into a muffle furnace for calcining, heating to a certain temperature at a certain heating rate, and maintaining for a period of time to obtain a conductive lanthanum-cobalt composite oxide; and S3, adding the lanthanum-cobalt composite oxide in the S2 into the strontium salt solution, stirring for 5-10 minutes, adding urea and citric acid, heating to a certain temperature, accelerating stirring to form gel, drying and roasting to obtain the electric heating strontium-lanthanum-cobalt composite catalyst. The prepared composite catalyst not only can effectively decompose VOCs, but also can keep high catalytic activity under the low-oxygen condition, and has good application prospects and economic benefits in the field of electric heating waste gas treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite catalysts, and in particular to a method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for purifying VOCs in a low-oxygen environment. Background Art

[0002] With the rapid development of industrialization, VOCs emissions have become one of the important sources of air pollution, especially in industries such as petrochemicals, pharmaceuticals, and coatings, which are often accompanied by extremely low oxygen content environments, such as high-temperature incineration processes or coking waste gas emissions with very little oxygen. These environments not only increase the difficulty of decomposing VOCs, but also place higher requirements on the stability and activity of catalysts. Therefore, the development of catalysts that can still effectively purify VOCs under ultra-low oxygen conditions is of great significance to the advancement of environmental protection technology.

[0003] At present, traditional VOCs purification catalysts mostly rely on redox-active metal oxides or precious metal catalysts, which can show good catalytic activity under conditions of high oxygen content. However, in ultra-low oxygen environments, the oxidation performance of these catalysts will drop significantly, or even have no catalytic effect, and they may lose structural stability due to lack of oxygen. In addition, due to the decrease in the lattice oxygen activity of the catalyst under low oxygen conditions, the migration rate of oxygen is also inhibited, thereby limiting its ability to oxidize VOCs. Therefore, designing a catalyst that can maintain high activity and high stability in a low oxygen environment has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a method for preparing an electric heating strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment. The prepared composite catalyst can not only effectively decompose VOCs, but also maintain a high catalytic activity under low oxygen conditions.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for purifying VOCs in a low oxygen environment comprises the following steps:

[0007] S1. Directly mix a certain proportion of lanthanum salt, cobalt salt, glucose and a small amount of deionized water, and stir for a period of time to form a viscous slurry to obtain a mixture;

[0008] S2, directly placing the S1 mixture in a muffle furnace for calcination, heating it to a certain temperature at a certain heating rate, and maintaining it for a period of time, to obtain a conductive lanthanum-cobalt composite oxide;

[0009] S3, adding the lanthanum cobalt composite oxide described in S2 to the strontium salt solution, stirring for 5 to 10 minutes, adding urea and citric acid, heating to a certain temperature, accelerating the stirring to form a gel, drying and calcining to obtain a strontium oxide-lanthanum oxide-cobalt oxide composite catalyst.

[0010] Preferably, in step S1, the lanthanum salt is a mixture of one or more of lanthanum nitrate, lanthanum chloride, lanthanum acetate and lanthanum sulfate; the lanthanum salt is preferably lanthanum nitrate.

[0011] Preferably, in step S1, the cobalt salt is a mixture of one or more of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt acetate; the cobalt salt here is preferably cobalt nitrate.

[0012] Preferably, in step S1, the molar ratio of lanthanum element, cobalt element and glucose in the lanthanum salt, cobalt salt and glucose is 1:(1-10):(1-16), and the content of the small amount of deionized water injected is 1%-10% of the total mass of the lanthanum salt, cobalt salt and glucose; the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min; here, the molar ratio of lanthanum element, cobalt element and glucose in the lanthanum salt, cobalt salt and glucose is preferably 1:4:8, and the content of the small amount of deionized water injected is 3% of the total mass of the lanthanum salt, cobalt salt and glucose; the stirring time is 30 min, and the stirring rate is 500 r / min.

[0013] Preferably, in step S2, the calcination heating rate is 1-10°C / min; the constant temperature maintained during calcination is 700-900°C, and the maintenance time of the constant temperature stage of calcination is 2-8h; the calcination heating rate is preferably 5°C / min; the constant temperature maintained during calcination is preferably 850°C, and the maintenance time of the constant temperature stage of calcination is preferably 5h.

[0014] Preferably, in step S3, the strontium salt is a mixture of one or more of strontium nitrate, strontium chloride, strontium acetate and strontium sulfate, and the concentration of the strontium salt solution is 0.01-0.1 mol / L; the strontium salt is preferably strontium nitrate, and the concentration of the strontium salt solution is preferably 0.03 mol / L.

[0015] Preferably, in step S3, the mass ratio of the strontium element in the strontium salt to the lanthanum-cobalt composite oxide, urea and citric acid is (0.05-0.1):1:(0.5-2):(0.1-1).

[0016] Preferably, in step S3, the temperature is 60-90°C, the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min; here the temperature is preferably 70°C, the stirring time is preferably 10-120 min, and the stirring rate is preferably 600 r / min.

[0017] Preferably, in step S3, the drying temperature is 60-80°C, the drying time is 6-8h, the roasting temperature is 500-600°C, and the roasting time is 3-5h; here the drying temperature is preferably 70°C, the drying time is preferably 7h, the roasting temperature is preferably 550°C, and the roasting time is preferably 4h.

[0018] By adopting the above technical solution: lanthanum oxide can improve the stability, sintering resistance and conductivity of cobalt oxide. Strontium oxide can create defect sites on the surface of cobalt oxide, promoting the catalyst to maintain good electrically driven lattice oxygen migration ability in a low oxygen environment. The prepared composite catalyst can be widely used in electrothermally driven exhaust gas treatment systems, especially in VOCs purification under ultra-low oxygen conditions. Its high structural stability and good electrically driven oxygen migration ability ensure the continuous high efficiency of the catalyst in a low oxygen environment, and can provide a feasible solution for VOCs treatment in high temperature and low oxygen environments such as petrochemicals, chemicals, and electronics. In the process of exhaust gas treatment, the catalyst can not only effectively decompose VOCs, but also maintain a high catalytic activity under low oxygen conditions. In addition, since no precious metal materials are used in the catalyst, it has a lower cost, so it has better economic benefits in achieving large-scale applications.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The lanthanum oxide in the present invention can improve the stability, sintering resistance and conductivity of cobalt oxide, and strontium oxide can create defect sites on the surface of cobalt oxide, promoting the catalyst to maintain good electrically driven lattice oxygen migration ability in a low oxygen environment. The composite catalyst prepared by the present invention can be widely used in electrothermally driven exhaust gas treatment systems, especially in VOCs purification under ultra-low oxygen conditions.

[0021] 2. The raw materials of the present invention are easily available, the preparation method is simple, and the catalyst prepared thereby can catalytically oxidize VOCs in an ultra-low oxygen environment.

[0022] 3. Compared with the use of traditional thermal catalytic materials, the present invention is more energy-efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XPS graph of the strontium lanthanum cobalt composite oxide catalyst prepared in Example 1 of the present invention;

[0024] Figure 2 The oxidation performance of the electrothermal catalyst prepared for all embodiments of the present invention on toluene in a high-purity nitrogen atmosphere. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0026] Embodiment 1:

[0027] (1) 10 mmol of lanthanum nitrate, 40 mmol of cobalt nitrate, and 80 mmol of glucose were directly mixed, and 0.9 g of deionized water was injected into the mixture, and stirred at 500 r / min for 30 min;

[0028] (2) placing the mixture in a muffle furnace and heating it to 850° C. at a heating rate of 5° C. / min, and calcining at the constant temperature for 5 h to obtain a lanthanum-cobalt composite oxide powder;

[0029] (3) Take 1g of the above-synthesized lanthanum cobalt composite oxide powder, 0.73g of urea, and 0.31g of citric acid and add them to 120mL of 0.03mol / L strontium nitrate solution, stir at 70°C and 600r / min for 30min to form a gel, then dry at 70°C for 7h, and finally calcine at 550°C for 4h to obtain a strontium lanthanum cobalt composite catalyst.

[0030] The XPS spectrum of the strontium lanthanum cobalt composite catalyst prepared in Example 1 is as follows: Figure 1 As shown in the figure, the distribution of strontium, lanthanum and cobalt can be seen. 1g of the catalyst prepared in Example 1 was heated in high-purity nitrogen (purity of 99.999%) at a reaction space velocity of 10000h -1 , 200℃ and toluene concentration of 1000mg / m 3 Electrothermal catalytic oxidation of toluene under the following conditions: Figure 2 As shown. Without current, the catalyst quickly loses its catalytic activity, but after adding 0.5A current, the catalyst maintains its catalytic activity at 54% after 50h. When the reaction current is increased, it exhibits excellent VOC ultra-low oxygen environment purification and removal activity, and its activity increases rapidly to more than 99%.

[0031] Embodiment 2:

[0032] (1) 5 mmol of lanthanum nitrate, 40 mmol of cobalt nitrate, and 80 mmol of glucose were directly mixed, and 0.28 g of deionized water was injected into the mixture, and stirred at 100 r / min for 10 min;

[0033] (2) placing the mixture in a muffle furnace and heating it to 700° C. at a heating rate of 1° C. / min, and calcining at the constant temperature for 8 h to obtain a lanthanum-cobalt composite oxide powder;

[0034] (3) Take 1g of the above-synthesized lanthanum cobalt composite oxide powder, 0.5g of urea, and 0.1g of citric acid and add them to 57.06mL of 0.01mol / L strontium nitrate solution, stir at 60°C and 100r / min for 120min to form a gel, then dry at 60°C for 8h, and finally calcine at 500°C for 5h to obtain a strontium lanthanum cobalt composite catalyst.

[0035] 1 g of the catalyst prepared in Example 2 was used and stirred in a high-purity nitrogen atmosphere (purity of 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 50% after 50 hours, showing excellent VOCs removal activity.

[0036] Embodiment 3:

[0037] (1) Mix 15 mmol of lanthanum chloride, 30 mmol of cobalt chloride, and 25 mmol of glucose, add 1.2 g of deionized water, and stir at 1000 r / min for 120 min;

[0038] (2) heating the mixture to 900° C. at a heating rate of 10° C. / min and calcining at the constant temperature for 2 h to obtain lanthanum-cobalt composite oxide powder;

[0039] (3) 1.5 g of the synthesized lanthanum cobalt composite oxide powder, 2 g of urea, and 1 g of citric acid were added to 17 mL of 0.1 mol / L strontium sulfate solution, stirred at 90 ° C and 1000 r / min for 10 min to form a gel, then dried at 80 ° C for 6 h, and finally calcined at 600 ° C for 3 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0040] 1 g of the catalyst prepared in Example 3 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 45% after 50h, showing excellent VOCs removal activity.

[0041] Embodiment 4:

[0042] (1) Take 5 mmol of lanthanum nitrate, 5 mmol of cobalt chloride, 10 mmol of cobalt nitrate, 5 mmol of cobalt sulfate, 5 mmol of cobalt acetate, and 15 mmol of glucose, mix them directly, inject 0.5 g of deionized water, and stir at 500 r / min for 25 min;

[0043] (2) placing the mixture in a muffle furnace and heating it to 800° C. at a heating rate of 3° C. / min, and calcining it for 4 h to obtain a lanthanum-cobalt composite oxide;

[0044] (3) 0.8 g of the synthesized lanthanum cobalt composite oxide, 0.5 g of urea, and 0.25 g of citric acid were added to 20 mL of a 0.02 mol / L strontium chloride solution, stirred at 75°C and 650 r / min for 35 min, dried for 6 h, and calcined at 530°C for 3 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0045] 1 g of the catalyst prepared in Example 4 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 52% after 50h, showing excellent VOCs removal activity.

[0046] Embodiment 5:

[0047] (1) Take 12 mmol of lanthanum sulfate, 12 mmol of cobalt sulfate, and 18 mmol of glucose and mix them directly, inject 1.0 g of deionized water, and stir at 600 r / min for 20 min;

[0048] (2) heating the mixture to 830° C. at a heating rate of 4° C. / min and calcining for 5 h to obtain lanthanum-cobalt composite oxide powder;

[0049] (3) 1.2 g of the synthesized lanthanum cobalt composite oxide powder, 0.8 g of urea, and 0.35 g of citric acid were added to 50 mL of 0.04 mol / L strontium acetate solution, stirred at 500 r / min at 60°C for 25 min, dried for 7 h, and calcined at 580°C for 5 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0050] 1 g of the catalyst prepared in Example 5 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 48% after 50h, showing excellent VOCs removal activity.

[0051] Embodiment 6:

[0052] (1) Take 5 mmol of lanthanum acetate, 50 mmol of cobalt acetate, and 30 mmol of glucose, mix them, add 1.5 g of deionized water, and stir at 700 r / min for 50 min;

[0053] (2) heating the mixture to 900° C. at a heating rate of 2° C. / min and calcining at the constant temperature for 7 h to obtain a lanthanum-cobalt composite oxide;

[0054] (3) 1.5 g of the synthesized lanthanum cobalt composite oxide, 1 g of urea, and 0.5 g of citric acid were added to 60 mL of 0.08 mol / L strontium nitrate solution, stirred at 700 r / min at 90° C. for 50 min, dried for 9 h, and calcined at 600° C. for 6 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0055] 1 g of the catalyst prepared in Example 6 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of 0.5A current and electrothermal catalytic oxidation of toluene, the toluene removal rate was maintained at 32% after 50 hours, showing excellent VOCs removal activity.

[0056] Embodiment 7:

[0057] (1) Take 3 mmol of lanthanum chloride, 24 mmol of cobalt chloride, and 22 mmol of glucose and mix them directly, inject 1.0 g of deionized water, and stir at 800 r / min for 15 min;

[0058] (2) placing the mixture in a muffle furnace and heating it to 880° C. at a heating rate of 7° C. / min, and calcining at the constant temperature for 6 h to obtain a lanthanum-cobalt composite oxide;

[0059] (3) 1 g of the synthesized lanthanum cobalt composite oxide, 0.6 g of urea, and 0.4 g of citric acid were added to 25 mL of a 0.07 mol / L strontium sulfate solution, stirred at 750 r / min at 85° C. for 40 min, dried for 6 h, and calcined at 570° C. for 4 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0060] 1 g of the catalyst prepared in Example 7 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 40% after 50h, showing excellent VOCs removal activity.

[0061] Embodiment 8:

[0062] (1) Take 2 mmol of lanthanum nitrate, 1 mmol of lanthanum chloride, 1 mmol of lanthanum acetate, 1 mmol of lanthanum sulfate, 35 mmol of cobalt nitrate, and 80 mmol of glucose, mix them, add 2.5 g of deionized water, and stir at 900 r / min for 30 min;

[0063] (2) heating the mixture to 800° C. at a heating rate of 5° C. / min and calcining at the constant temperature for 6 h to obtain lanthanum-cobalt composite oxide;

[0064] (3) 1.8 g of the synthesized lanthanum cobalt composite oxide, 1 g of urea, and 0.5 g of citric acid were added to 50 mL of 0.09 mol / L strontium nitrate solution, stirred at 80°C and 500 r / min for 50 min, dried for 8 h, and calcined at 500°C for 8 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0065] 1 g of the catalyst prepared in Example 8 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 The toluene removal rate was maintained at 42% after 50 h of electrocatalytic oxidation of toluene under the conditions of 0.5 A current, showing excellent VOCs removal activity.

[0066] Embodiment 9:

[0067] (1) Take 5 mmol of lanthanum nitrate, 30 mmol of cobalt nitrate, and 70 mmol of glucose, mix them, add 2.35 g of deionized water, and stir at 400 r / min for 60 min;

[0068] (2) heating the mixture to 850° C. at a heating rate of 10° C. / min and calcining at the constant temperature for 8 h to obtain a lanthanum-cobalt composite oxide;

[0069] (3) 1.5 g of the synthesized lanthanum cobalt composite oxide, 1 g of urea, and 0.5 g of citric acid were added to 60 mL of 0.1 mol / L strontium nitrate solution, stirred at 300 r / min at 60° C. for 50 min, dried for 12 h, and calcined at 500° C. for 8 h to obtain a strontium lanthanum cobalt composite oxide catalyst.

[0070] 1 g of the catalyst prepared in Example 9 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of electrothermal catalytic oxidation of toluene and 0.5A current, the toluene removal rate was maintained at 45% after 50h, showing excellent VOCs removal activity.

[0071] Comparative Example 1: A method for preparing strontium oxide, comprising the following steps:

[0072] (1) Dissolve 10 mmol of strontium nitrate directly into 30 mL of deionized water;

[0073] (2) stirring the mixed solution in (1) at 300 r / min, adjusting the pH of the mixed solution to 10 with NaOH, and continuing stirring at 300 r / min for 30 min to obtain a precipitate;

[0074] (3) The precipitate obtained in (2) is heated to 4550°C in a muffle furnace at a heating rate of 5°C / min and maintained at this temperature for 3 hours. The resulting product is a strontium oxide catalyst.

[0075] 1 g of the catalyst prepared in Example 1 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200°C, and toluene concentration 1000 mg / m 3 Under the above conditions, the electrothermal catalytic oxidation of toluene was carried out, and it was found that it was not conductive and had no catalytic oxidation effect on toluene.

[0076] Comparative Example 2: Preparation of Lanthanum Cobalt Oxide

[0077] (1) Take 10 mmol lanthanum nitrate, 40 mmol cobalt nitrate, and 20 mmol glucose and mix them directly;

[0078] (2) The mixture was placed in a muffle furnace and heated to 850°C at a heating rate of 5°C / min, and calcined at the constant temperature for 5 hours. The obtained product was the catalyst.

[0079] 1 g of the catalyst prepared in Example 2 was used and stirred in a high-purity nitrogen atmosphere (purity: 99.999%) at a reaction space velocity of 10000 h -1 , temperature 200℃, toluene concentration 1000mg / m 3 Under the conditions of 0.5A current, the initial toluene oxidation efficiency was 10%, but the toluene oxidation activity soon disappeared.

[0080] Table 1 shows the test results of each embodiment and control example.

[0081]

[0082] In summary, the lanthanum oxide in the present invention can improve the stability, sintering resistance and conductivity of cobalt oxide, and strontium oxide can create defect sites on the surface of cobalt oxide, promoting the catalyst to maintain good electrically driven lattice oxygen migration ability in a low oxygen environment. The composite catalyst prepared by the present invention can be widely used in electrothermally driven exhaust gas treatment systems, especially in VOCs purification under ultra-low oxygen conditions.

[0083] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for purifying VOCs in a low oxygen environment, characterized in that: The steps include: S1. Directly mix a certain proportion of lanthanum salt, cobalt salt, glucose and a small amount of deionized water, and stir for a period of time to form a viscous slurry to obtain a mixture; S2, directly placing the S1 mixture in a muffle furnace for calcination, heating it to a certain temperature at a certain heating rate, and maintaining it for a period of time, to obtain a conductive lanthanum-cobalt composite oxide; S3, adding the lanthanum cobalt composite oxide described in S2 to the strontium salt solution, stirring for 5 to 10 minutes, adding urea and citric acid, heating to a certain temperature, accelerating the stirring to form a gel, drying and calcining to obtain a strontium oxide-lanthanum oxide-cobalt oxide composite catalyst.

2. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for purifying VOCs in a low oxygen environment according to claim 1, characterized in that: In step S1, the lanthanum salt is a mixture of one or more of lanthanum nitrate, lanthanum chloride, lanthanum acetate and lanthanum sulfate.

3. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S1, the cobalt salt is a mixture of one or more of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt acetate.

4. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S1, the molar ratio of lanthanum element, cobalt element and glucose in the lanthanum salt, cobalt salt and glucose is 1:(1-10):(1-16), and the content of a small amount of deionized water injected is 1%-10% of the total mass of the lanthanum salt, cobalt salt and glucose; the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min.

5. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S2, the calcination heating rate is 1-10°C / min; the constant temperature maintained during the calcination is 700-900°C, and the maintenance time of the calcination constant temperature stage is 2-8h.

6. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S3, the strontium salt is a mixture of one or more of strontium nitrate, strontium chloride, strontium acetate, and strontium sulfate, and the concentration of the strontium salt solution is 0.01-0.1 mol / L.

7. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S3, the mass ratio of the strontium element in the strontium salt to the lanthanum-cobalt composite oxide, urea and citric acid is (0.05-0.1):1:(0.5-2):(0.1-1).

8. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for purifying VOCs in a low oxygen environment according to claim 1, characterized in that: In step S3, the temperature is 60-90° C., the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min.

9. The method for preparing an electrically heated strontium lanthanum cobalt composite catalyst for VOCs purification in a low oxygen environment according to claim 1, characterized in that: In step S3, the drying temperature is 60-80°C, the drying time is 6-8h, the roasting temperature is 500-600°C, and the roasting time is 3-5h.